Design and Development of Active Physiotherabot for Stroke Patients - Parmar, Vimalkumar A; Kothari, Kartik D (International Journal of Computer Sciences and Engineering, 2019)
The paper describes about the research work carried out for design and development of a robotic glove that will be able to find out the finger movement in a mathematical form. Further, this data can be used for treating semi-paralysed patients. In Stroke patients where body parts movement cannot take place entirely or partially can take the benefit of proposed system. Flex Sensors have been used for each finger in order to design the proposed system. Arduino-UNO software is being used for the coding of sensors. Collected mathematical data can be stored for exercise selection criteria or to develop a passive exercise model.